Sistem Pendukung Keputusan Pemilihan Pegawai Honorer Kelurahan Menerapkan Metode MOORA - Naomi Permai Siburian; Lusi Sahriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Temporary employee is an employee who works for a government or private agency or institution, but their employment status is not officially appointed, they must go through a rigorous selection and recruitment process like permanent employees. Based on observations on the selection of honorary employees, there is a problem in determining the selection of honorary employees to be completed based on the criteria set by the Sitirejo II Lurah Office. Within the Kelurahan Sitirejo II institution, of course there are Honorary Employees, and to make all of this happen is not easy because there is still a selection process in the appointment of Honorary Employees. However, until now the Sitirejo II Village does not yet have a specific method for selecting Honorary Employees, so that in the implementation of the election it often encounters problems and requires quite a long time because it must have all the requirements to become an Honorary Employee in the Sitirejo II Village. From the problems encountered, because with Honorary Employees who have qualification standards, the productivity of the kelurahan must be maintained and increased. In this study it can be concluded that a decision support system is needed that can analyze a number of selected Honorary Employees. The method used in this decision support system is the Moora method. This Decision Support System has the goal of providing information, guiding, providing predictions, and directing solution options to users of information so they can make better decisions. These reasons make the creation of a model in decision making an important matter, so that the decisions taken are accurate, careful and of course profitable for those concerned. Based on the calculations using the MOORA method, the authors get the result that the best Decision Support System for Selection of Honorary Employees in Sitirejo II Village is the A6 alternative in the name